Comparative analyses on dynamic performances of photovoltaic–thermal solar collectors integrated with phase change materials. (1st January 2017) - Su, Di; Jia, Yuting; Alva, Guruprasad; Liu, Lingkun; Fang, Guiyin
Graphical abstract: Highlights: The dynamic model of photovoltaic–thermal collector with phase change material was developed. The performances of photovoltaic–thermal collector are performed comparative analyses. The performances of photovoltaic–thermal collector with phase change material were evaluated. Upper phase change material mode can improve performances of photovoltaic–thermal collector. Abstract: The operating conditions (especially temperature) of photovoltaic–thermal solar collectors have significant influence on dynamic performance of the hybrid photovoltaic–thermal solar collectors. Only a small percentage of incoming solar radiation can be converted into electricity, and the rest is converted into heat. This heat leads to a decrease in efficiency of the photovoltaic module. In order to improve the performance of the hybrid photovoltaic–thermal solar collector, we performed comparative analyses on a hybrid photovoltaic–thermal solar collector integrated with phase change material. Electrical and thermal parameters like solar cell temperature, outlet temperature of air, electrical power, thermal power, electrical efficiency, thermal efficiency and overall efficiency are simulated and analyzed to evaluate the dynamic performance of the hybrid photovoltaic–thermal collector. It is found that the position of phase change material layer in the photovoltaic–thermal collector has a significant effect on the performance of the photovoltaic–thermal collector. The results indicate that upper phase change material mode in the photovoltaic–thermal collector can significantly improve the thermal and electrical performance of photovoltaic–thermal collector. It is found that overall efficiency of photovoltaic–thermal collector in 'upper phase change material' mode is 10.7% higher than that in 'no phase change material' mode. Further, for a photovoltaic–thermal collector with upper phase change material, it is verified that 3 cm-thick phase change material layer is excellent both in electrical and thermal performance.